Gender balance management: the case of Malaysia - Sieh, Lee Mei Ling; Ong, Fon Sim (Penerbit Universiti Kebangsaan Malaysia, 1995)
The relationship between gender balance in management and organisational performance was examined by asking if a more gender balanced management team would result in better performance or higher productivity. Findings indicated that there were fewer women managers than men in managerial positions. When compared to their male counterparts, women managers tend to be more meticulous, careful, patient and cooperative.